The experiment of double solar energy by reflection light method - Julajaturasirarath, S.; Jonburom, W.; Pornsuwancharoen, N. (My University, 2012)
This paper we propose a novel conception design that can be used to generate double power the new optical solar energy using refection solar light propagating within photo voltage PV system. By the four mirror refection upon the solar cell occurs the solar energy have double energy for 10 W to 20 W. The temperature effect relation the power solar energy in this paper have clear concept the heat by water sink and winding flow for under solar cell in discussion section. © 2010 Published by Elsevier Ltd.
Keywords: Double solar power; PV and Solar energy; Solar power